Dependence of upstream SOL density shoulder on divertor neutral pressure observed in L-mode and H-mode plasmas in the EAST superconducting tokamak. (17th June 2021) - Yan, N.; Chen, L.; Xu, G.S.; Wu, X.Q.; Liu, S.C.; Wang, Y.F.; Meng, L.Y.; Hu, G.H.; Zhao, N.; Lan, H.; Naulin, V.; Nielsen, A.H.; et al.
Abstract: Upstream density profiles in the scrape-off layer (SOL) have been examined in low-confinement mode (L-mode) and high-confinement mode (H-mode) plasmas in the EAST superconducting tokamak. A weak density shoulder forms in the near SOL region in upper single-null configurations when the neutral pressure measured at the lower divertor exceeds a threshold value of 2 × 10 −2 Pa in L-mode plasmas. When the neutral pressure is below this threshold, the weak density shoulder is absent and the sidebands of the lower hybrid waves associated with SOL parametric instabilities are reduced. Active detachment control with neon–deuterium seeding demonstrate that the weak density shoulder can form before the onset of the outer divertor detachment as long as the neutral pressure is above the threshold. Furthermore, no remarkable expansion of a shoulder is observed during divertor detachment, suggesting that divertor detachment is not a necessary condition for the formation or growth of a density shoulder. Through the increase in neutral pressure in the lower divertor by an order of magnitude, the weak shoulder was observed to expand into the far SOL and reach the leading edge of the limiter. The results in L-mode discharges identified the neutral pressure in the lower divertor as a primary factor for the formation of an SOL density shoulder in the upper single-null discharges. For the type-I ELMy H-mode plasmas, a similar density shoulder was detected during the inter-ELM phase when the neutral pressure in the lower divertor exceeded a threshold value of 4 × 10 −2 Pa. On the other hand, the shoulder was absent when the divertor neutral pressure went below this threshold even though the plasma discharge was conducted with a higher core line-averaged density and divertor collisionality. This is consistent with the observations in L-mode plasmas. The neutral particle ionization of the working gas is thus believed to play a key role during the formation of the SOL density shoulder in the EAST tokamak.